DIGITAL LEADERSHIP FOR SUSTAINABLE ORGANIZATIONAL TRANSFORMATION: A SYSTEMATIC LITERATURE REVIEW - Rahdini Rizki Saragih; Suci Indah Syafitri; Nindy Erisma (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
Digital transformation has fundamentally reshaped how organizations create value, compete, and sustain performance in dynamic environments. However, successful transformation depends not only on technological investment but also on leadership capabilities that align digital initiatives with organizational vision, culture, and sustainability objectives. This study aims to examine the evolution, theoretical foundations, and strategic role of digital leadership in enabling sustainable organizational transformation through a Systematic Literature Review (SLR). Relevant studies on digital leadership, digital transformation, dynamic capabilities, organizational agility, sustainability, and digital readiness were systematically analyzed using thematic synthesis to identify key patterns, theoretical perspectives, and emerging research directions. The findings indicate that digital leadership has evolved from a technology-focused concept into a strategic capability involving digital mindset, agility, data-driven decision-making, innovation, and change management. Digital leaders act as strategic orchestrators who facilitate sustainable transformation by developing organizational capabilities, enhancing digital readiness, and supporting human-centered change processes. This study contributes an integrated conceptual framework that positions digital leadership as a strategic organizational capability and provides theoretical and practical insights for advancing sustainable digital transformation research and practice.